Pneumothorax in patients with severe combined immunodeficiency. Issue 4 (30th May 2014) - Hoshino, Akihiro; Imai, Kohsuke; Ohshima, Yusei; Yasutomi, Motoko; Kasai, Masashi; Terai, Masaru; Ishigaki, Keiko; Morio, Tomohiro; Miyawaki, Toshio; Kanegane, Hirokazu
Abstract Background Most infants with pneumothorax have underlying conditions. Pneumocystis jirovecii pneumonia (PCP) frequently occurs in patients with severe combined immunodeficiency (SCID). The aim of this study was to determine clinical features of PCP‐associated pneumothorax in SCID patients. Methods The medical records of four SCID patients with pneumothorax were retrospectively reviewed. Results All four patients were diagnosed as having SCID at the time of contracting PCP. All patients received mechanical ventilation because of severe respiratory failure. Only one patient was successfully extubated and was alive following hematopoietic stem cell transplantation (HSCT); of the remaining patients, however, two died of respiratory failure, and one patient died of early HSCT‐related complications. Conclusions Pneumothorax associated with PCP can occur in SCID patients, and they may have a poor prognosis. If pneumothorax occurs in infants, both respiratory management and prompt investigation of the underlying conditions are needed, considering the possibility of PCP associated with SCID.